An Analysis of Inflation Effects on Purchasing Power among Low-Income Households in Urban Areas - Junaidi Hartawan; Maria Gonzalez (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Inflation remains a persistent macroeconomic challenge that directly affects household welfare, particularly among low-income populations in urban areas. This study aims to analyze the impact of inflation on purchasing power among low-income households by synthesizing empirical evidence from cross-country studies. A qualitative systematic review approach was employed using recent peer-reviewed articles, reports, and repositories. The findings indicate that inflation significantly reduces real income, alters consumption patterns, and increases economic vulnerability. Households tend to prioritize essential goods while reducing expenditures on non-essential items, leading to declining living standards. The study also finds that inflation disproportionately affects low-income groups due to their limited financial resilience and higher expenditure share on necessities. These results highlight the importance of targeted policy interventions such as income support, price stabilization, and social protection programs. The study contributes to the literature by providing a comparative analysis of inflation impacts across different urban contexts.